Application of E-Performance and Compensation Systems To Employee Performance Through Motivation As An Intervening Variable - Rifqiansyah, Achmad Irfan; Yuliantini, Tine (Journal Research of Social Science, Economics, and Management, 2023)
Advanced human resources (HR) are required for an organization to achieve its goals and objectives. There is a need for human resource management so that the implementation of activities runs optimally by evaluating employee performance. The research method used was causal quantitative, which aims to analyze the effect of implementing e-performance systems and compensation on employee performance through motivation as an intervening variable. The research population consists of employees serving in the Indonesian Navy. The Naval Personnel Staff totals 113 employees. The Slovin method was used to calculate the sample, which yielded a sample of 89 employees. Data collection methods in the form of primary data come from questionnaires, and secondary data is derived from agencies. Methods of data analysis using descriptive analysis as well as structural equation model partial least squares (SEM-PLS) analysis. The results of the analysis show that the implementation of the e-performance system affects motivation, compensation affects motivation, the implementation of the e-performance system has affected employee performance, compensation has affected employee performance, motivation has affected employee performance, the implementation of the e-performance system has affected employee performance through motivation as an intervening variable, and compensation does not affect employee performance through motivation as an intervening variable.